Trend of anaesthesia research from SAARC countries. A decade’s bibliographic analysis of indexed journals of Pakistan - Karima Karam; Ausaf Ahmed Khan; Muhammad Irfan Akhtar; Samie Asghar Dogar; Fauzia Anis Khan (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the contribution of member countries of the South Asian Association for Regional Cooperation towards anaesthesia research. Method: The retrospective study was conducted at Department of Anaesthesia, Aga Khan University from January 2018 to June 2018 and comprised literature search to identify published articles related to anaesthesia, critical care and pain research contributed by authors from member countries of the South Asian Association for Regional Cooperation region and published in Pakistani indexed journals between January 2007 and December 2016. Data was analysed using SPSS 19. Results: Of the 183 articles extracted, 179(97.8%) were contributed from Pakistan and 4(2.2%) from India. Overall, there were 50(27%) randomised controlled trials, 38((20%) case reports and 36(19.5%) observational studies. There was 1(0.5%) collaborative study involving researchers from two member countries. Conclusions: The contribution to anaesthesia, critical care and pain research was not ideal from the member countries of the South Asian Association for Regional Cooperation. Key Words: South Asia, Research, Anaesthesiology, Pakistan.